Clinical pharmacists in palliative care: effects on drug therapy and drug expenses Apotheker auf der Palliativstation: Auswirkung auf Arzneimitteltherapie und Therapiekosten - Wolf, Carolin; Dörje, Frank; Klein, Carsten; Ostgathe, Christoph (Schmerz, 2019)
Background: The effect of integrating clinical pharmacists in German palliative care units with regard to the quality of drug therapy and drug costs has yet not been evaluated. Objectives: This work aims to assess the number of pharmaceutical interventions (PI) and the cost-benefit ratio of a clinical pharmacist taking part in the interprofessional patient care team on an inpatient palliative care unit in Germany. Methods: The number of and underlying reasons for the pharmacist-led recommendations were recorded and analyzed over a 1-year period. In addition, the respective drugs and the acceptance rate of recommendations were assessed. To evaluate the cost-benefit ratio, the financial savings in the provision of drugs were recorded and compared with the expenses for the clinical pharmacy service. Results: A total of 245 PI were performed. Most frequently, the pharmacist advised physicians on drug choices and drug dosages. The acceptance rate was 93%. The cost savings in the provision of drugs covered 83% of the expenses for the clinical pharmacy service. Conclusion: The results indicate that the integration of a clinical pharmacist is well suited to optimizing the interprofessional treatment of distressing symptoms with a beneficial economic outcome in palliative care. Consequently, the permanent integration of a clinical pharmacist on an inpatient palliative care unit seems to be beneficial and advisable.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Cost-benefit analysis; Palliative medicine; Pharmaceutical services; Symptom control; Terminal care